Tax obligations incurred before and after the death of a sole propietorship company in Peru - López Raygada, Pedro Enrique Velásquez (2019)
Analyzing the doctrine that supports the regulation in the Tax Code of the institutions of joint and several tax liability and the transfer of tax obligations, it is verified that there is an inadequate and contradictory normative treatment to the tax obligations incurred before and after the death of the owner of a sole proprietorship in Peru. We have made an explanatory, qualitative, descriptive and substantive analytical type research, based on a mental and logical analysis. Both institutions should be adequately regulated to reduce conflict and increase legal certainty and predictability in tax matters.